2017
DOI: 10.1590/0102-33062017abb0100
|View full text |Cite
|
Sign up to set email alerts
|

The effects of salinity on growth and survival of mangrove seedlings changes with age

Abstract: Six wide-ranging mangrove species, Rhizophora apiculata, R. mucronata, Avicennia marina, A. offi cinalis, Bruguiera gymnorrhiza, and B. sexangula, were selected to study the growth and survival of seedlings under three contrasting salinity treatments over a 30-week period: low (3-5psu), moderate (15-17psu) and high (33-36psu). Seedlings grown under high salinity exhibited signifi cantly lower performance (p<0.05) in survival rates, cumulative shoot height, mean growth rates, mean total leaf area, and mean dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 44 publications
4
78
1
7
Order By: Relevance
“…The reduced hydraulic conductivity could secondarily depend on SC of the plants as SC of the R plants grown in the 50% WHC and high salinity was significantly lower while the highest was recorded in the plants grown in the freshwater treatment. Several studies reported that high stomatal conductance in R. mucronata was recorded in freshwater condition and it was reduced with the increase of salinity and similar results were recorded for other mangrove species as well (Naidoo 1985;Aziz and Khan 2000;Kodikara et al 2017b). Moreover smaller leaf area is also a strategy to reduce water loss from plants under water deficit conditions (Ball 1988;Brugnoli and Lauteri 1991).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The reduced hydraulic conductivity could secondarily depend on SC of the plants as SC of the R plants grown in the 50% WHC and high salinity was significantly lower while the highest was recorded in the plants grown in the freshwater treatment. Several studies reported that high stomatal conductance in R. mucronata was recorded in freshwater condition and it was reduced with the increase of salinity and similar results were recorded for other mangrove species as well (Naidoo 1985;Aziz and Khan 2000;Kodikara et al 2017b). Moreover smaller leaf area is also a strategy to reduce water loss from plants under water deficit conditions (Ball 1988;Brugnoli and Lauteri 1991).…”
Section: Discussionsupporting
confidence: 64%
“…Based on our preliminary measurements, the salinity of water in the tanks was checked once in every two days using a hand refractometer (ATAGO S/Mill-E, Japan) and adjusted the salinity when necessary (added aged tap water when the level of salinity was higher than the expected and seawater was added when the salinity was lower). Commercially available fertilizer was also applied (in the form of pellets) once a month by providing the same amount per pot (Adopted from Jayatissa et al 2008;Dissanayake et al 2014;Kodikara et al 2017b). …”
Section: Methodsmentioning
confidence: 99%
“…Basyuni et al (2018) found an optimum seedling dry weight at 15 ppt and a more bell-shaped salt tolerance curve. In the longerterm study conducted by Kodikara et al (2018) the low salinity treatment (3-5 ppt) provided the best conditions for seedling growth of R. apiculata and 5 other mangrove species until 15-20 weeks of age, but afterwards the optimum salinity shifted towards 15-17 ppt. Such plasticity of salinity tolerance during ontogeny has been described repeatedly for mangrove species (Kathiresan and Bingham, 2001;Alleman and Hester, 2011).…”
Section: Design Conceptsmentioning
confidence: 96%
“…Information on the salt tolerance of Rhizophora apiculata or its fundamental niche in terms of salinity is only available from experiments in which seedlings were grown over a limited time period at a range of salinities (Moorthy and Kathiresan, 1995;Ball et al, 1997;Basyuni et al, 2018Basyuni et al, , 2019Kodikara et al, 2018). However, the results of these experiments vary considerably in detail.…”
Section: Design Conceptsmentioning
confidence: 99%
“…For instance, a change was reported in the total pigments of A. marina subjected 2 International Journal of Forestry Research to leaf spot disease (Alternaria alternate) [18]. High levels of salinity negatively affected leaf area (LA), leaf specific area (LSA), and leaf weight [10,19]. The ecophysiological traits, no doubt, are genetically based.…”
Section: Introductionmentioning
confidence: 99%